Neurological melioidosis presenting as intracranial abscess - Deepak Madi (Indian Journal of Pathology and Microbiology, 2016)
Melioidosis is an emerging disease in our country caused by the bacteria Burkholderia pseudomallei. Melioidosis can virtually affect any organ. It has varying clinical presentations ranging from pneumonia to fatal sepsis. Central nervous system (CNS) involvement in melioidosis is rare. We present a case of CNS melioidosis from South India. As the incidence of diabetes is increasing in our country varying manifestations of melioidosis will be seen in routine clinical practice. Melioidosis should be considered in the differential diagnosis of intracranial abscess and meningoencephalitis, especially in diabetics.